El estudio de la integración regional y del regionalismo en américa latina: Entre la influencia europea y el pensamiento propio (2023)
The objective of this paper is to analyze the evolution of the study of regional integration and regionalism in Latin America. The main argument is that the theories developed to explain integration in Europe have been widely used in Latin America, generating a problem of Eurocentrism that has marked the regional debates. This has happened despite the fact that Latin America has produced a theory of its own to evaluate regionalism and regional integration, expressions of which are the ECLAC’s structuralism and the theory about autonomy. To analyze this problem, it is used a qualitative methodology based on a systematic bibliographic review of the theoretical debates on integration and regionalism. © 2018, Universidad Nacional de Colombia. All rights reserved.